Maternal Profile and Neonatal Outcomes of Pregnant Women Infected with HIV / AIDS in Banda Aceh on 2017-2019 - Cut Meurah Yeni; Riza Sufriadi (Britain International of Exact Sciences (BIoEx) Journal, 2020)
This aims of the study is to find out Profile of Maternal and Neonatal Outcomes in Pregnant woman Infected by HIV/AIDS. This research is a descriptive study, looking at maternal characteristics and infant outcomes of pregnant women infected with HIV / AIDS in RSUDZA. Based on the author's research on maternal profile and neonatal outcomes in pregnant women infected with HIV / AIDS in Banda Aceh, there were 14 cases during 2017-2019. There were 1 babies born with low birth weight, 1 stillbirth, 10 out of 14 vigorous babies, 10 cesarean births, 3 preterm births and 8 patients with no known CD4 + status.